Proximity extension assay proteomics and renal single cell transcriptomics uncover novel urinary biomarkers for active lupus nephritis - Li, Yaxi; Tang, Chenling; Vanarsa, Kamala; Thai, Nga; Castillo, Jessica; Lea, Gabrielle Alexis Braza; Lee, Kyung Hyun; Kim, Soojin; Pedroza, Claudia; Wu, Tianfu; Saxena, Ramesh; Mok, Chi Chiu; et al. (Journal of autoimmunity, 2024)
To identify urinary biomarkers that can distinguish active renal involvement in Lupus Nephritis (LN), a severe manifestation of systemic lupus erythematosus (SLE). Urine from 117 subjects, comprised of inactive SLE, active non-renal lupus, active LN, and healthy controls, were subjected to Proximity Extension Assay (PEA) based comprehensive proteomics followed by ELISA validation in an independent, ethnically diverse cohort. Proteomic data is also cross-referenced to renal transcriptomic data to elucidate cellular origins of biomarkers. Systems biology analyses revealed progressive activation of cytokine signaling, chemokine activity and coagulation pathways, with worsening renal disease. In addition to validating 30 previously reported biomarkers, this study uncovers several novel candidates. Following ELISA validation in an independent cohort of different ethnicity, the six most discriminatory biomarkers for active LN were urinary ICAM-2, FABP4, FASLG, IGFBP-2, SELE and TNFSF13B/BAFF, with ROC AUC ≥80%, with most correlating strongly with clinical disease activity. Transcriptomic analyses of LN kidneys mapped the likely origin of these proteins to intra-renal myeloid cells (CXCL16, IL-1RT2, TNFSF13B/BAFF), T/NK cells (FASLG), leukocytes (ICAM2) and endothelial cells (SELE). In addition to confirming the diagnostic potential of urine ALCAM, CD163, MCP1, SELL, ICAM1, VCAM1, NGAL and TWEAK for active LN, this study adds urine ICAM-2, FABP4, FASLG, IGFBP-2, SELE, and TNFSF13B/BAFF as additional markers that warrant systematic validation in larger cross-sectional and longitudinal cohorts. •PEA Proteomics validates active LN biomarkers, including urine ALCAM, CD163, MCP1, SELL, ICAM1, VCAM1, NGAL, and TWEAK.•Urinary biomarkers with >80% accuracy for active LN include ICAM2, FABP4, FASLG, IGFBP-2, SELE, and TNFSF13B/BAFF.•Proteins appear to arise from myeloid (CXCL16, IL-1RT2, TNFSF13B/BAFF), T/NK (FASLG), and endothelial (SELE) cells.